2019
DOI: 10.1080/13504622.2019.1637822
|View full text |Cite
|
Sign up to set email alerts
|

Engaged environmental science for underserved youth

Abstract: The National Institute for Environmental Health Sciences has called for targeted efforts to engage underserved youth in environmental education programs that support environmental literacy and contribute to the development of a diverse workforce pipeline for environmental science-related occupations. Evidence suggests that career knowledge among low income and minority youth is more likely to be incompatible with post-secondary educational opportunities than other racial and ethnic groups. One approach to atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Our evaluation of the Mosquito Mappers internship was an opportunity to assess not only the success of a new, virtual internship opportunity, but to also investigate how place-based citizen science contextualized in a project of students' choosing may influence young people in STEM. Research in STEM learning has shown that place-based learning is an effective way to help students understand the real-world connections between scientific research and human lives (Avery 2013;Cruz et al, 2019;Kirsch et al, 2019). By coupling place-based citizen science to a virtual internship, Mosquito Mappers interns were able to connect to their communities while building the science process skills that can contribute to successful secondary and post-secondary STEM coursework and careers.…”
Section: Introductionmentioning
confidence: 99%
“…Our evaluation of the Mosquito Mappers internship was an opportunity to assess not only the success of a new, virtual internship opportunity, but to also investigate how place-based citizen science contextualized in a project of students' choosing may influence young people in STEM. Research in STEM learning has shown that place-based learning is an effective way to help students understand the real-world connections between scientific research and human lives (Avery 2013;Cruz et al, 2019;Kirsch et al, 2019). By coupling place-based citizen science to a virtual internship, Mosquito Mappers interns were able to connect to their communities while building the science process skills that can contribute to successful secondary and post-secondary STEM coursework and careers.…”
Section: Introductionmentioning
confidence: 99%
“…Engaging youth also benefits researchers, as young people bring creativity, new ideas, and energy to research endeavors. 98 101 Returning research results: Returning research results to study participants and the broader community is critical to help people understand and reduce their exposures. Researchers should ensure materials and messages are culturally appropriate for the community.…”
Section: Discussionmentioning
confidence: 99%
“…Engaging youth also benefits researchers, as young people bring creativity, new ideas, and energy to research endeavors. 98 101 …”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, there has been a growing body of peer-reviewed literature related to climate change and its associations with human and ecological health and safety-related issues, including EJ. However, to date, excluding studies and reviews about educating adults in colleges/universities and groups of professionals such as health care providers, there has been limited peer-reviewed research in English specifically about educating HS students [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%